2018
DOI: 10.1038/s41388-017-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss in the fallopian tube induces hyperplasia and ovarian tumor formation

Abstract: The signaling events involved in the onset of ovarian cancer from the fallopian tube epithelium (FTE) are crucial for early detection and treatment of the disease, but they remain poorly defined. Conditional homozygous knockout of PTEN mediated by PAX8-cre recombinase was sufficient to drive endometrioid and serous borderline ovarian carcinoma, providing the first model of FTE-derived borderline tumors. In addition, heterozygous PTEN deletion in the FTE resulted in hyperplasia, providing a model to study early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 53 publications
1
52
0
1
Order By: Relevance
“…Human fallopian tube cells transformed in vitro produce tumours that are morphologically and genetically similar to HGSOC [15][16][17]. Genetically engineered mouse OC models containing mutations commonly found in HGSOC such as p53, PTEN, BRCA1, BRCA2, and Rb1 in tubal secretory cells have shown the phenotype of STIC formation and emergence of HGSOC [18][19][20]. Clinical studies have confirmed that the majority of women who undertook salpingo-oophorectomy due to the presence of BRCA1, 2 mutations had STICs in the fallopian tube.…”
Section: Different Origins Of Ocmentioning
confidence: 97%
“…Human fallopian tube cells transformed in vitro produce tumours that are morphologically and genetically similar to HGSOC [15][16][17]. Genetically engineered mouse OC models containing mutations commonly found in HGSOC such as p53, PTEN, BRCA1, BRCA2, and Rb1 in tubal secretory cells have shown the phenotype of STIC formation and emergence of HGSOC [18][19][20]. Clinical studies have confirmed that the majority of women who undertook salpingo-oophorectomy due to the presence of BRCA1, 2 mutations had STICs in the fallopian tube.…”
Section: Different Origins Of Ocmentioning
confidence: 97%
“…These mice developed STIC lesions and serous carcinomas 31 . Interestingly, loss of PTEN alone in the fallopian tube (via Pax-8-Cre) was sufficient to generate endometrioid and serous borderline tumors 34 . This raises the possibility of fallopian tube origins for some Type I tumors and non-HGS tumors.…”
Section: Histologic Types Of Ovarian Cancermentioning
confidence: 99%
“…This study highlights the numerous possibilities offered by the non-coding part of the genome in the development of HGSC and gives a glimpse of the pathway and the ceRNA network by which MAGI2-AS3 positively restricts the activity of HGSC cells. The mRNAs HOXA5, MTSS1, PTEN, and RECK are reported to have important tumor-suppressive roles in OC [42,45,63,64], though their role in HGSC is not specifically shown. This study has not only experimentally validated the regulation of the expression of tumor-suppressive mRNAs such as HOXA5, MTSS1, PTEN, and RECK by MAGI2-AS3 in HGSC but also has suggested a network of how various pathways converge to aid in tumor suppression.…”
Section: Discussionmentioning
confidence: 99%